Prevalence and associated risk factors of stunting too early: analysis of the 2020 Rwanda demographic and health survey - Jeanine Condo; Raphael Ndahimana; Melissa Uwase; Roger Muragire; Alliance Uwase; Edith Uwamahoro; Bwiza Flavia; Elysee Niyonganyira; Ayinkamiye Esperance; Divine Umutesi Rusa; Marie Josée Mwiseneza; Absolomon Gashaija; et al. (BMJ Nutrition, Prevention & Health)
Background Stunting in young children continues to be a public health concern in Rwanda. The effect of stunting in the first 1000 days of life has long-term consequences, including decreased brain development and a higher risk of developing diseases later in life. To design proper interventions, identifying the risk factors of stunting too early is paramount. The study thus aimed to identify the prevalence of stunting too early (6–23 months) and its associated risk factors.Methods The research study analysed secondary data from the nationally conducted demographic health survey of 2019–2020, which was analysed by using bivariate analysis and multivariable logistic regression models to determine the factors associated with stunting that occurred too early. P value of <0.05, regression coefficients and their 95% CI were used to assess the level of significance as well as insights related to the strength and direction of the relationship between being stunted too early and other covariates.Results A total of 1180 children aged 6–23 months were included in the analysis. The overall prevalence of stunting too early was 30% with a 95% CI of 27.4%–32.6%. Moreover, the prevalence of stunting was 29.0%, 20.0%, 23.0% and 35% among the 6 months, 7–8 months, 9–12 months and 13–23 months age groups, respectively. After adjusting for potential confounding variables, the following factors were independently associated with stunting too early: being male (aOR:2.3; 95% CI:1.68 to 3.00), not currently being breastfed (aOR:1.97, 95% CI:1.21 to 3.19), mothers aged 25–34 and more than 34 years (aOR:1.64; 95% CI:1.11 to 2.43) and (aOR:1.63; 95% CI:1.07 to 2.47), respectively, households with poor wealth index (aOR:2.61; 95%CI: 1.72 to 3.09), child age group of 13–23 months (aOR:2.00; 95% CI:1.14 to 5.51) and small child size at birth (aOR:2.36; 95% CI:1.42 to 3.92).Conclusions The prevalence of stunting too early was high, and the factors significantly associated with it were the sex and age of the child, the mother’s age, low socio-economic status and small child size at birth. There is a need to address those factors through campaigns of health education, emphasis on girls’ education for their empowerment and strengthening of nutritional programme implementation.